To determine the frequency of Group B Streptococcal colonization of vagina in women at 35-37 week pregnancy - Sadia Azmat, Faiza Iqbal, Shabnam Tahir, Mariam Khalid, Sadia Mustafa, Wajeeha Asghar Alvi, Sadia Azmat, Faiza Iqbal, Shabnam Tahir, Mariam Khalid, Sadia Mustafa, Wajeeha Asghar Alvi (Journal of Rawalpindi Medical College, 2022)
BACKGROUND: Group B streptococci (GBS) is the usually present in vaginal canal in micro-flora, which usually do not exhibit any symptoms. Instead, in pregnancy, there are certain situations in GBS colonization in vagina, which may lead to several complications. OBJECTIVE: To determine the frequency of Group B Streptococcal colonization of vagina in women at 35-37 week pregnancy. STUDY DESIGN: Cross sectional survey SETTING: Antenatal clinic, Shalamar Hospital Lahore STUDY DURATION: 6 month i.e. From: 05-09-2014 to 06-03-2015 SUBJECTS & METHODS: 350 Booked Patients attending antenatal clinic at Shalamar hospital at 35-37 weeks of pregnancy for routine antenatal checkup were included. Lower vaginal swabs were taken without speculum using sterilized disposable cotton swab and transported to Amies Agar jell and transported to microbiology lab within 24 hours. Laboratory report was collected and reviewed by researcher regarding positive or negative culture for GBS. Patients with positive GBS culture were given intrapartum antibiotics. RESULTS: In our study, out of 350 cases, with the mean age of 26.92+4.84 years. Frequency of GBS colonization of vagina in women at 35-37 week pregnancy was recorded in 12.29% while remaining 87.71% had no findings of the morbidity. CONCLUSION: It was concluded that the frequency of GBS colonization of vagina in women at 35-37 week pregnancy is not very higher and in accordance with other regions of our country, but routine screening may further decline its incidence. KEYWORDS: Pregnancy, last trimester, Group B Streptococcal colonization of vagina